2007
DOI: 10.1097/01.ta.0000251593.32396.df
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Index in Trauma Patients

Abstract: (1) Several factors alter HRV in patients; (2) when HRV was indexed for some of these factors, its specificity and efficiency were improved for predicting a discrete pathologic state in trauma patients, i.e. (+) or (-) cranial CT scans; (3) the algorithm can incorporate other factors to further refine the diagnostic and/or prognostic ability of HRV as a noninvasive clinical tool; (4) this concept should be applicable to any other HRV measurement technique or outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…2,15Y17,21,22 Subsequent studies in prehospital and in-hospital trauma patients have corroborated these results. 6,8,14 For example, a recent report demonstrated that reduced HRV was an independent predictor of morbidity and mortality in 216 hemodynamically stable trauma patients with evidence of traumatic brain injury upon hospital arrival. 6 Importantly, however, the aforementioned study acknowledges that HRV analysis was completed a few hours to 3 days after initial measurement, which limits usefulness for clinical decision making.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2,15Y17,21,22 Subsequent studies in prehospital and in-hospital trauma patients have corroborated these results. 6,8,14 For example, a recent report demonstrated that reduced HRV was an independent predictor of morbidity and mortality in 216 hemodynamically stable trauma patients with evidence of traumatic brain injury upon hospital arrival. 6 Importantly, however, the aforementioned study acknowledges that HRV analysis was completed a few hours to 3 days after initial measurement, which limits usefulness for clinical decision making.…”
Section: Discussionmentioning
confidence: 96%
“…Traditional HRV measurement was determined using time-domain analysis, specifically SDNN [SD of the normal-to-normal RRI]. 14,16,17 Clinical management of the patient occurred at the discretion of the treating physician who was blinded to the real-time study data.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these systems use a combination of sensors or changes in HR variability to determine when a person is in the early stages of hemorrhagic shock. [23][24][25][26] The results of early studies are promising, but these systems are not widely available. Until they do become available, TVS will continue to be the main way that patients at risk for dying from hemorrhagic shock are identified.…”
Section: Discussionmentioning
confidence: 96%
“…Others have reported similar associations between decreased complexity and poor outcomes in trauma patients [6,7] and critically ill populations [8][9][10]. However, little is known about how and when response to injury results in reduced heart rate complexity, or how injury etiology might mediate the observed relationship between reduced complexity and increased mortality.…”
Section: Introductionmentioning
confidence: 81%